ANALISIS PORTOFOLIO SAHAM DENGAN MENGGUNAKAN CAPM-MAYERS PADA SAHAM YANG TERDAFTAR DALAM INDEX LQ45 PERIODE 2018-2021 - ARIYANTI, RINI; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika, 2025)
The CAPM-Mayers method is a method used to calculate the expected return and risk, by involving asset prices that cannot be marketed in the capital market. The purpose of this study was to determine the effect of non-marketable assets on the risk value and expected return value in a stock portfolio using the CAPM-Mayers method. The data used in this study are monthly closing price data for Asuransi Bina Dana Arta Tbk shares and 10 selected company data from the highest volume of stock sales listed in the LQ45 Index for the period January 2018 to December 2021. The standard CAPM has a large risk value, while the CAPM- Mayers has a small risk value and standard CAPM has a small expected return value while CAPM-Mayers has a large expected return value. The research results obtained are that assets that cannot be marketed affect the decrease in the value of risk and increase in the value of the expected return in a stock portfolio .